Host Dependent-Transposon for a Plasmid Found in Aeromonas salmonicida subsp. salmonicida That Bears a catB3 Gene for Chloramphenicol Resistance - Pierre-Étienne Marcoux; Sabrina A. Attéré; Valérie E. Paquet; Maude F. Paquet; Sarah B. Girard; Judith Farley; Michel Frenette; Antony T. Vincent; Steve J. Charette (MDPI AG, 2023)
Plasmids that carry antibiotic resistance genes occur frequently in Aeromonas salmonicida subsp. salmonicida, an aquatic pathogen with severe consequences in salmonid farming. Here, we describe a 67 kb plasmid found in the A. salmonicida subsp. salmonicida Strain SHY15-2939 from Quebec, Canada. This new plasmid, named pAsa-2939 and identified by high throughput sequencing, displays features never found before in this bacterial species. It contains a transposon related to the Tn21 family, but with an unusual organization. This transposon bears a catB3 gene (chloramphenicol resistance) that has not been detected yet in A. salmonicida subsp. salmonicida. The plasmid is transferable by conjugation into Aeromonas hydrophila, but not into Escherichia coli. Based on PCR analysis and genomic sequencing (Illumina and PacBio), we determined that the transposon is unstable in A. salmonicida subsp. salmonicida Strain SHY15-2939, but it is stable in A. hydrophila trans-conjugants, which explains the chloramphenicol resistance variability observed in SHY15-2939. These results suggest that this bacterium is likely not the most appropriate host for this plasmid. The presence of pAsa-2939 in A. salmonicida subsp. salmonicida also strengthens the reservoir role of this bacterium for antibiotic resistance genes, even those that resist antibiotics not used in aquaculture in Québec, such as chloramphenicol.